Denning, metabolic suppression, and the realisation of ecological opportunities in Ursidae. (2nd March 2021) - Fowler, Nicholas L.; Spady, Thomas J.; Wang, Guiming; Leopold, Bruce D.; Belant, Jerrold L.
Abstract: Through realisation of ecological opportunities, populations and species can experience relaxed selection pressures, facilitating ecological release and leading to rapid speciation and morphological diversification. Behavioural plasticity in response to environmental change contributes to diversification by exposing individuals to novel conditions through their interactions with resources or dispersal to new areas. Despite strong theoretical support, demonstrations of this evolutionary process are rare. The family Ursidae is the product of one or more adaptive radiations following the Miocene–Pliocene transition. Denning behaviour associated with over‐winter seclusion, fasting, and parturition coinciding with seasonally decreased food availability appears to be paraphyletic in Ursidae phylogenies. However, female bears of all species undergo varying degrees of seclusion and fasting during parturition and early post‐natal care, which is not consistent with periods of seasonally decreased food availability. As denning behaviour is tightly linked to fitness through energetics and reproduction, these behaviours are suspected to be under strong selection. Mechanisms responsible for the observed variability among species, populations, and individuals have not been explored. In this review, we detail the evolutionary history of extinct and extant Ursidae regarding expression of denning behaviour and as a function of realised ecological opportunities. We compare behaviours across Ursidae and contextualise our results within extant species ecology. We demonstrate the role of relaxed extrinsic and intrinsic factors in the expression of metabolic suppression among Ursidae species, and across populations and reproductive groups, through the realisation of ecological opportunities. In doing so, we propose a more refined consideration of and perspective on this behaviour and provide a mechanism for the adaptive radiation in Ursidae. Abstract : Realisation of ecological opportunities reduces selective on pressures on seasonal food availability in Ursidae lineages, facilitating apparent reductions in metabolic suppression during denning behaviour.